Ubiquitous skill opens opportunities for talent and expertise development - Araújo, Duarte; Roquette, João; Davids, Keith (Frontiers in Sports and Active Living, 2023)
In this article we aim to define and present the complementary nature of talent, skill and expertise. Human daily life is replete with expressions of skillful behaviours while interacting with the world, which in specific socio-culturally defined domains, such as sport and work, demand a specialization of such ubiquitous skill. Certain manifestations of ubiquitous skill are identified by experts from the specialized domain of sport with the label of “talent”. In this paper we propose that “talent” is thus socially defined, considered identifiable at an early age and forms the basis for selection and entry at the starting point in domains like sport. Once an individual, defined as “talented” enters the “pathway” for participating in the sport domain, there begins an intense socialization process where training, evaluation, institutionalization and framing takes place for continued development of such talent. This is the formalised process of working on ubiquitous skills refining and changing them into specialized skills in sport. An ecological dynamics rationale is used to explain that this specialization approach is developed through a process of expert skill learning, which entails the stages of exploration and education of intention stabilization and perceptual attunement, and exploitation and calibration. Skill learning aims to develop potentiality and its expression in actuality, i.e., how learning is expressed in contextualized expert performance.